The consignment stock case for a vendor and a buyer with delay-in-payments. (August 2016) - Zahran, Siraj K.; Jaber, Mohamad Y.; Zanoni, Simone
Highlights: Two-level supply chain with consignment stock agreement. Equal-interval payment strategy was considered. Consignment stock with/without the delay in payment was considered. Paying the vendor after the permissible period was shown to be the most profitable. Abstract: Inventory Management (IM) techniques help in minimizing (maximizing) the total cost (profit) of a supply chain and enhance its performance. Different models have been developed within the supply chain area to manage inventories and solve related issues (i.e. logistics and transportation). Consignment stock (CS) is an IM technique that has been shown to improve supply chain performance, where a vendor uses its buyer's warehouse to store its items. The buyer pays the vendor once the items are withdrawn from the consigned inventory. This paper investigates the CS policy in a two-level (vendor–buyer) supply chain when it is permitted to delay payments. This is a business practice found in CS contracts. An equal-interval equal-payment scheme is considered, and three scenarios of delayed payments have been developed. The first scenario (base model) does not consider delay-in-payments, where the second (interest-free) and the third (with interest) do. The results showed that offering the buyer a permissible period to settle its account is better for the system than paying the vendor at the time of the invoice. In addition, the third scenario, where the buyer pays the vendor after the permissible period and is charged interest, was shown to be the most profitable for the supply chain system considered.